iPhone game development - Craft, Chris; McElveen, Jamey (Indianapolis, Ind. Wiley, 2010)
"If you've always wanted to develop a cool iPhone game application and sell it for big bucks, this book is for you. iPhone Game Development covers all technical and commercial bases, from how to sign up for the Apple Development Program, master the development tools in the iPhone SDK, publish your game to the App Store, and convince people to buy it. You'll find full coverage of Cocoa Touch and other great features of the iPhone SDK, plus pages of real-world examples with step-by-step explanations. The book also includes loads of royalty-free code you can use for commercial development"--Resource description page.
Part I: Beginning iPhone Programming -- Pt. II: Creating Simple iPhone Applications -- Pt. III: Shall We Play a Game? -- Pt. IV: Advanced Technical and Business Programming Concepts -- Pt. V: Appendixes.
Prof. Rommel Feria (recommending faculty) : CS Dept.
Keywords: iPhone (Smartphone) -- Programming; Mobile games -- Programming